Developing impactful entrepreneurial teaching using a business model framework - Kenneth L. Stenkjær; Kristian Brøndum Kristiansen; Jesper Chrautwald Sort; Morten Lund (Journal of Business Models (JOBM), 2021)
This paper provides insights towards the development of an impactful entrepreneurial course called New Venture Creation. The course is based on the principals of Lean Start-up methodology but modified to encompass the demands from a Higher Educational Institution. The course has shown positive results among students, externals and incubators.
Keywords: 650; Teaching; Entrepreneurship; Business Models